The role of graphene Oxide’s aromatic rings in activated carbon made from banana leaves (ACBL) and Fe3O4 in hydrogen production - Dewi Sartika; Denny Widhiyanuriyawan; Agung Sugeng Widodo; Purnami; I.N.G Wardana (Carbon Resources Conversion)
Fe3O4 is an internal magnet that can work as a medium for the electrolyte solution in electrochemical hydrogen production to facilitate electron movement. When Fe3O4 is combined with activated carbon made from banana leaves (ACBL), electron transfer occurs between the ACBL aromatic ring and Fe3+ ions from solved Fe3O4, which increases the solution’s conductivity and finally produces more hydrogen. ACBL is a biomass catalyst used as a free parameter to increase the Fe3O4 magnetic field in the solution. The Fe3O4 was synthesized using the coprecipitation method, while ACBL was obtained through an activation process to produce graphene oxide. Graphene oxide in ACBL was characterized using Scanning Electron Microscopy (SEM) EDX, Fourier Transform Infra-Red (FTIR), Brunauer, Emmett, and Teller (BET), and TEM (Transmission Electron Microscopy). BET was used to determine the surface area of ACBL. Hydrogen was produced using the electrolysis method. The SEM results showed that the elemental content of graphene oxide in ACBL was 72.47 %. The graphene oxide in ACBL had a positive charge represented by a bright color on the sample surface. The positive charge was due to the FTIR O-H and C-O groups working with Fe3O4. BET analysis showed that the average pore diameter of ACBL was 1.68 nm. The largest hydrogen production results were obtained at ACBL 200 mesh, which was 15.5 ml. ACBL from abundant biomass has magnetic and electrical potential within its aromatic ring. As the aromatic ring interacts with the magnetic field of Fe3O4, the electromagnetic field of the solution is strengthened. As a result, hydrogen production increases.